Natural Killer Cells Adapt to Cytomegalovirus Along a Functionally Static Phenotypic Spectrum in Human Immunodeficiency Virus Infection - Holder, Kayla A.; Lajoie, Julie; Grant, Michael D. (Frontiers in Immunology, 2018)
Human- and virus-derived cytokines that potentially affect natural killer (NK) cell function are produced early after human cytomegalovirus (HCMV) infection. Later events drive accumulation of functionally enhanced CD57posNKG2Cpos adapted NK cells. Here, we investigated NK cell adaptation to HCMV along a continuum progressing from acute activation through maturation and memory formation towards functional exhaustion. We found NK cell cytotoxicity increased following exposure to a soluble factor in conditioned media collected 24 hours after HCMV infection (HCMVsn). Increases in NK cell cytotoxicity were completely abrogated by blocking type I interferon (IFN) receptors and equivalent responses occurred with IFN-2 alone at the same concentration as present in HCMVsn. Increased cytotoxicity occurred for HCMV-seronegative and seropositive donors, with mean 38% and 29% boosts in natural and antibody-dependent cell-mediated cytotoxicity (ADCC) respectively. To study longer term effects of HCMV infection, we focused on three groups of human immunodeficiency virus (HIV)-infected subjects distinguished by either HCMV-seronegative or -seropositive status with high (> 20%) versus low (< 6%) fractions of their NK cells expressing NKG2C. The NK cells of all HIV-infected groups responded to HCMVsn and IFN-2. Neither HCMV status, nor phenotypic evidence of adaptation to HCMV infection significantly affected mean levels of ADCC or CD16-mediated NK cell degranulation and IFN-γ production. Levels of IFN-γ production correlated significantly with the fraction of NK cells lacking FcRIγ1 (FcRγ), but not with the fraction of NK cells expressing NKG2C. We found negligible expression of the exhaustion markers Lag-3 and PD-1 on NK cells in any of the groups and no significant difference between groups in the fraction of NK cells expressing Tim-3, which was unaffected by CD16 stimulation. Relative to the total NK cell population, responses of Tim-3-expressing cells to CD16 stimulation were variably compromised in the HCMV seronegative and seropositive groups. In general, NK cell function in response to signaling through CD16 was well preserved in HIV infection and although HCMV had a clear effect on NK cell FcRγ and NKG2C expression, there was little evidence that the level of adaptation to HCMV infection affected CD16-dependent NK cell signaling in HIV infection.